The effects of reward and punishment on the performance of ping-pong ball bouncing - Yin, Cong; Wang, Yaoxu; Li, Biao; Gao, Tian (Frontiers in Behavioral Neuroscience, 2024)
Reward and punishment modulate behavior. In real-world motor skill learning, reward and punishment have been found to have dissociable effects on optimizing motor skill learning, but the scientific basis for these effects is largely unknown. In the present study, we investigated the effects of reward and punishment on the performance of real-world motor skill learning. Specifically, three groups of participants were trained and tested on a ping-pong ball bouncing task for three consecutive days. The training and testing sessions were identical across the three days: participants were trained with their right (dominant) hand each day under conditions of either reward, punishment, or a neutral control condition (neither). Before and after the training session, all participants were tested with their right and left hands without any feedback. We found that punishment promoted early learning, while reward promoted late learning. Reward facilitated shortterm memory, while punishment impaired long-term memory. Both reward and punishment interfered with long-term memory gains. Interestingly, the effects of reward and punishment transferred to the left hand. The results show that reward and punishment have different effects on real-world motor skill learning. The effects change with training and transfer readily to novel contexts. The results suggest that reward and punishment may act on different learning processes and engage different neural mechanisms during real-world motor skill learning. In addition, highlevel metacognitive processes may be enabled by the additional reinforcement feedback during realworld motor skill learning. Our findings provide new insights into the mechanisms underlying motor